ARES: aircraft propulsion integration - Tsentseris, Michail (Cranfield University, 2013)
The combat aircraft and the gas turbine engine interact with one another. These interactions have become of even greater significance than previously due to the fact that the modern aircraft have increased requirements in terms of thrust, efficiency, reliability and ease of maintenance. Issues that affect the performance and operational capability of combat aircraft are the aircraft aerodynamic characteristics, propulsion system performance and the airframe/engine matching. This study focuses on the evaluation of the propulsion system of modern jet powered combat aircraft and combines computations with the existing integration methodology. The main objective of this study is the update of ARES method (aircraftengine performance tool for combat aircraft) so as to be feasible the incorporation of new data in the calculations of the program. The update contains: • the establishment of a procedure that can be used for the calculation of the additional drag that a external load (tanks, bombs, missiles, pods) contribute in the total aircraft drag, • the modification of ARES method in order to integrate the additional drag of the external loads in the program calculations, • the creation of a procedure that will be used for the calculation of the thrust deductions due to installation effects. The information that can be received from this study are valuable because can be used in the evaluation of the engine performance, can give the opportunity for further engine studies such as the structural and thermal analysis, component sizing and geometry, life consumption and of course can make apparent if a specific aircraftengine system is capable of accomplishing a demanded operating requirement. The final results of the study led to the general conclusion that the total aircraft drag and the demanded uninstalled net thrust increased with the addition of external tanks in the aircraft. The fuel consumption was higher for the configuration with the two tanks and was noticed an increase of the TET which is proportional to the number of the used external tanks (max TET increases at least 0.8% per tank). Additionally was extracted the conclusion that the addition of an external wing tank increases the amount of the consumed fuel at least 3.5%.